MELIHAT ADALAH PERCAYA: KEKUATAN PEMBELAJARAN VISUAL DALAM ILMU PENGETAHUAN ALAM - Nurjannah; Mira Andriyani (Al-Ikram : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
At the present time education is very important, starting from that, it is appropriate for educators in this case teachers to think about various efforts to be able to maximize all efforts so that students are able and willing to always learn and develop knowledge, especially in science learning.Natural science is one of the subjects that focuses on the era of Industry 4.0 today, because the development of technology causes changes in the environment. Realizing the importance of this, it requires educators to be able to teach natural science to students well. The use of visual media is one of the right choices in helping students understand natural science. Because with visual media, natural science objects that cannot be seen can be seen, thus creating a belief that natural science is important and useful. The power of visual learning in natural science includes helping students understand teaching materials and providing motivation in learning by presenting objects from discussions in reality. Keywords: Natural Science, Learning, Media, Visual